Patient satisfaction of pharmaceutical care of primary care centers at Ministry of Health in Saudi Arabia - Alomi, Yousef Ahmed; Kurdy, Lina; Aljarad, Zainab; Basudan, Hamid; Almekwar, Banan; Almahmood, Sharefia (Journal of Pharmacy Practice and Community Medicine)
Objective: The study examined patient satisfaction with pharmaceutical care of selected domains at primary care centers of Ministery of Health in Saudi Arabia as a pilot study. Methods: It is a cross-sectional self-administered survey of pharmaceutical care at selected primary care centers. The survey contains two parts; the first part was demographic data about the patients, the second part was several domains about various pharmaceutical care services. This survey had distributed to three primary care centers at the east providence, middle region, and east providence. The 5-point Likert response scale system used with Arabic and English language. All data and variables analyzed by Microsoft Excel program version 10 and statistical package of social science (SPSS) version 20. Results: The study sample size was 862 with response rate 45.85%, Of that 77.3% were male, 22.62% were female. The average age was 39.6. The majority of patients were in very good health 319 (37%) and good health status 338 (39.21%). The highest score of patient satisfaction with domains was Medication Availability, patient counseling, and Pharmacist and Patient Relationships. The lowest score of patient satisfaction with domains was pharmacy communication and medication reconciliation. The patients showed overall satisfied with pharmaceutical care at primary care center pharmacies with average score 4.01 of the maximum score of 5, without any difference between three centers (p>0.05). Conclusion: Patient satisfaction with pharmaceutical care was very goods. It reflected good pharmacy services offered to the patients with emphasis to patient counseling to patients and pharmacist patient relationships. The pharmacy communication and medication reconciliation should be reviewed to prevent drug-related problems and improve pharmaceutical care at MOH primary care centers in Saudi Arabia.
Keywords: Satisfaction; Patient; Pharmaceutical Care; Primary Care Center; Ministry of Health; Saudi Arabia